Pengembangan Karir Terhadap Kinerja Perawat dalam Pendokumentasian Asuhan Keperawatan - Laili Fahriza; Mohammad Basit; Angga Irawan (LPPM STIKES Guna Bangsa, 2023)
Background: The problem of failure of human resource management can affect the achievement of the objectives of profit and survival the hospital, especially the performance of nurses, is an indicator of the results of the implementation of the nursing care delivery process contained in documenting nursing care Improving nurse performance in documenting nursing care supported through career development which includes the organization's policy work experience training education work achievement and organizational loyalty The implementation of career development and performance can support the process of improving the quality of hospital services. Purpose: To discover the correlation between career development and nurses’ performance on nursing application documentation in Sari Mulia Hospital Banjarmasin. Methods: This research used the association analysis method with quantitative data, and was using a cross sectional study design. Twenty respondents were selected using the total sampling technic. Result: Result of this research was obtained using the Spearman Statistical Test and it was found that the significant score (2-tailed) was 0.032<0.05 which indicates that there was a correlation between career development and nurses’ performance on nursing application documentation. Conclusion: This study shows that career development had a significant relationship with nurses' performance in documenting nursing care through training, education, work experience, organizational policies, work performance and organizational loyalty. This means that a good career development has an influence on the performance of nurses in the process of documenting care. Keywords: Career development, nursing application documentation, nurses’ performance.